Identifying Intermediates of Sequential Electron and Hydrogen Loss from a Dicarbonylcobalt Hydride Complex1. Issue 26 (10th May 2013) - Krafft, Michael J.; Bubrin, Martina; Paretzki, Alexa; Lissner, Falk; Fiedler, Jan; Záliš, Stanislav; Kaim, Wolfgang
<x xml:space="preserve">Abstract</x> Step by step: Electron‐ and hydrogen‐transfer steps are documented IR‐spectroelectrochemically and structurally for the H2‐producing oxidation of a dicarbonylcobalt hydride complex modified by the sterically protecting 1, 1′‐bis(diisopropylphosphino)ferrocene. The series complements the mechanism discussed for water‐reducing cobalt compounds with less π‐accepting ligands.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>